2014
DOI: 10.4331/wjbc.v5.i4.437
|View full text |Cite
|
Sign up to set email alerts
|

Identification of host miRNAs that may limit human rhinovirus replication

Abstract: Taken together, our results suggest that pathological changes in microRNA expression, as already reported for asthma or chronic obstructive pulmonary disease have the potential to affect Rhinovirus replication and therefore may play a role in virus-induced exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 88 publications
1
38
0
Order By: Relevance
“…However, in vitro studies have demonstrated that has-miR155 transfection suppresses RV replication in the human cell line BEAS-2B (derived from normal human bronchial epithelial cells). [ 23 ] In this elegant work Bondanese and colleagues also observed viral RNA co-immunoprecipitated with argonaute 2 protein (crucial component of the miR silencing complex) confirming the functional direct action of miRs against RV. In agreement with our current findings, bioinformatics predictions and subsequent experiments demonstrated that hsa-miR155 is the key miR orchestrating host immune responses against RV.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, in vitro studies have demonstrated that has-miR155 transfection suppresses RV replication in the human cell line BEAS-2B (derived from normal human bronchial epithelial cells). [ 23 ] In this elegant work Bondanese and colleagues also observed viral RNA co-immunoprecipitated with argonaute 2 protein (crucial component of the miR silencing complex) confirming the functional direct action of miRs against RV. In agreement with our current findings, bioinformatics predictions and subsequent experiments demonstrated that hsa-miR155 is the key miR orchestrating host immune responses against RV.…”
Section: Discussionmentioning
confidence: 76%
“…We focused on the targetome analysis of hsa-miR-155 , given our current observations and recent evidence demonstrating the antiviral effect of hsa-miR-155 against RV in vitro . [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-128 and miR-155 miRNAs were identified as possible regulators of the innate immune response against RV-1B [33], since they have as targets the genetic material from RV. A report demonstrated that gene silencing of these miRNAs increases RV replication by~50% [34]. miR-23b is involved in the immune response against RV, as it downregulates LPR5 and VLDLR transmembrane receptor expression [4].…”
Section: Rhinovirus (Rv)mentioning
confidence: 99%
“…Third, host miRNAs can also directly target pathogen mRNAs to regulate pathogen replication, latency, and virulence. For example, miR‐128 and miR‐155 can decrease the replication of human rhinovirus by binding to viral RNA . Several cellular miRNAs can target viral mRNA genes in resting CD4 + cells to maintain HIV‐1 latency .…”
Section: Mirnas Regulate T Cell Immunity During Pathogen Infectionmentioning
confidence: 99%